Workshop Implementasi PTK Berbasis Lesson Study Kompetensi Keahlian Teknik Konstruksi Properti di SMK Negeri 3 Jombang - Evany Iqrammah; Titin Sundari; Akmam Mutrofin (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2023)
Abstract Teachers who are involved in the world of education are noble people because they are obliged to educate and educate the nation's children in accordance with the instructions contained in the fourth paragraph of the 1945 Constitution. Based on observations, there are still many teachers who experience difficulties in writing scientific papers or conducting Classroom Action Research. Teachers still have a lot of understanding and expertise in preparing PTK, so our service team is currently making improvements so that teachers have the skills to prepare PTK. In the PTK writing workshop, the teachers, especially those currently in Group IVb and Group IVa, feel the need for PTK, while among young teachers there is a strong desire to get to know PTK in order to improve quality. The purpose of the service is to train Construction and Property Engineering Skills Competency teachers to conduct Classroom Action Research as a solution to learning problems. After attending the training, teachers are no longer allergic to Classroom Action Research because they are increasingly able to utilize various effective and efficient learning models. Keywords: Vocational Teachers, Lesson Study, Classroom Action Research Abstrak Guru yang berkecimpung dalam dunia pendidikan merupakan orang yang mulia karena berkewajiban mendidik dan mendidik anak bangsa sesuai dengan perintah yang terdapat dalam pembukaan alinea keempat UUD 1945. Berdasarkan hasil observasi, masih banyak guru yang mengalami kesulitan dalam menulis karya ilmiah atau melakukan Penelitian Tindakan Kelas. Guru masih memiliki banyak pemahaman dan keahlian dalam penyusunan PTK, sehingga tim pengabdi kami sedang melakukan perbaikan agar para guru memiliki keterampilan untuk menyusun PTK. Dalam kegiatan workshop penulisan PTK para guru khususnya yang saat ini berada Golongan IVb dan Golongan IVa merasa perlu adanya PTK, sedangkan di kalangan guru muda ada keinginan yang kuat untuk mengenal PTK guna meningkatkan mutu. Tujuan dilaksanakannya pengabdian untuk melatih guru-guru Kompetensi Keahlian Teknik Konstruksi dan Properti melakukan Penelitian Tindakan Kelas sebagai solusi permasalahan pembelajaran. Setelah mengikuti pelatihan, guru tidak lagi alergi dengan Penelitian Tindakan Kelas karena semakin mampu memanfaatkan berbagai model pembelajaran yang efektif dan efisien. Kata kunci: Guru SMK, Lesson Study, Penelitian Tindakan Kelas